Teaching Mormon Studies at a School of Theology and a Public University - Rees, Robert A. (Mormon studies review, 2015)
The article offers brief information on Graduate Theological Union (GTU) focused on offering Mormon studies in Berkeley, California. It mentions that GTU wanted to include Mormonism in its academic program. It mentions that the course on Mormonism includes Introduction to Mormonism, Sacred Texts of the Latter-day Saints and Mormonism: Emergence of a New World Religion.